Growth frontiers in international business - Ibeh, Kevin; Tolentino, Paz Estrella E., 1960-; Janne, Odile E. M.; Liu, Xiaming (Palgrave Macmillan, 2017)
The ACADEMY OF INTERNATIONAL BUSINESS (UK and Ireland Chapter) Published in association with the UK and Ireland Chapter of the Academy of International Business Reflecting the aim of the 43rd AIB-UKI Conference on re-invigorating the still faltering global economy, this new book brings together fresh and interdisciplinary perspectives on avenues for further advancing the growth of international enterprises and the global economy. Growth frontiers in International Business includes contributions from a diverse number of established and emergent IB scholars, who richly illustrate contemporary international business growth frontiers. The book presents discussion and thought into four main foci; policy frontiers, emerging market frontiers, innovation pathways and ethical growth avenues.
Keywords: International business enterprises -- Congresses.; Corporations -- Growth -- Congresses.; elektronické knihy; electronic books